PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT. PEGADAIAN KOTA PEKANBARU - Putra, Eka; Zabaldi, Nabilah Fitri (Eko dan Bisnis: Riau Economic and Business Review, 2022)
Human Resources (HR) is the most basic problem in determining the achievement of the goals of an organization in accordance with what has been set, but sometimes it can also be one of the obstacles in the development and development of an organization. Organizational commitment is an attitude of respect, respect, obedience, and obedience to the applicable regulations, both written and unwritten and being able to carry out them and not evading receiving sanctions if he violates the duties and authorities given to him. In general, the purpose of this study is to determine the effect of organizational commitment on the performance of employees of PT. Pegadaian Pekanbaru City Branch. The number of samples in this study were 34 employees. From the results of the overall validity test of the statement items between the organizational commitment variable and the performance variable, it is declared valid because the value of rcount > rtable (0.3388). The results of simple linear regression obtained the value of Y = 5.548 + 0.896X. From the results of the t-test, the tcount (7.982)> from the ttable value (2.03693) with a significant level of 0.000 <0.05 means that the organizational commitment variable has an effect on the performance variable. And the value of the coefficient of determination R2 is 0.666, meaning that the contribution or the magnitude of the influence of organizational commitment on performance is 0.666 or 66.6% while the remaining 33.4% is influenced by other variables that are ignored or not examined in this study